IMPROVEMENT OF CHILDREN’S LANGUAGE SKILLS THROUGH SINGING ACTIVITIES - Lily Yuntina (Dialectical Literature and Educational Journal, 2021)
Education as a dynamic process in which children develop according to the inner terms of their lives, with their "voluntary work" when placed in an environment that is prepared to give them freedom of self-expression. One aspect that needs to be developed from an early age is language, the most ideal for learning a language other than the mother tongue (first language). The purpose of this research was to find out and get information about children's language improvement through singing activities, Research Subject was students at Kindergarten Al Marjan Bekasi. The type of research methodology is a descriptive qualitative method. Source of the data for this research took from the principal and teachers. The object were 26 students of Group B. Data collection technique through the results of the observations, interviews, documentation and field notes as data supporting. The type of observation used is passive participation observation. The stages of data analysis were consisted of data before, data in the field, and after completion of the field. Data validity checking techniques are based on credibility, transferability, dependability, confirmability. In checking the validity researcher used a degree of trust, with platform learning at home using social media as a communication tool between teachers and students. The result of this research, there is a significant increasing children’s language skill through singing activities.